Tafsir Tarbawi: Tinjauan Al-Quran Tentang Term Kecerdasan - Qowim, Agus Nur (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
The Koran as a perfect guide, it should provide ample room to search for terms related to intelligence. Intelligence cannot be separated from discussions of reason (ta'qilun). A smart human being is characterized, he always thinks (yatafakkarun) in order to achieve goodness and truth. In addition, intelligent humans will ponder and permeate every second of life that will continue to roll (yatadabbarun). Intelligent man will easily absorb and understand every knowledge he learns (yatafaqqahun). In addition to optimizing physical things, an intelligent human being does not forget to remember his God, he will always dhikr (yatadzakkarun).